ANALISIS IMT SISWA KELAS 7 SMPN 12 SEMARANG TERHADAP PROGRAM MAKANAN BERGIZI GRATIS (MBG) - Ajeng Putri Atma Dhani; Bertika Kusuma Prastiwi; Dian Ayu Zahraini (Journal of Physical Activity and Sports (JPAS), 2025)
Balanced nutrition plays a crucial role in supporting the growth and development of school-aged children. The government has introduced the Free Nutritious Meal Program (MBG) as an effort to improve students’ nutritional intake, particularly at the elementary and junior high school levels. This study aims to analyze the effect of the MBG program on the nutritional status of seventh-grade students at SMPN 12 Semarang using Body Mass Index (BMI) as the main indicator. This research employed a quantitative approach with a cross-sectional survey method. Data were collected through measurements of body weight and height from 254 students participating in the MBG program. The measurements were then used to calculate BMI, which was classified based on WHO standards. The findings revealed that 76.38% of students had normal nutritional status, 7.48% were underweight, 13.39% were overweight, and 2.76% were obese. Overall, the results indicate that the Free Nutritious Meal Program (MBG) contributes positively to the students’ nutritional status.